German Reading and Writing Competencies Using Google Classroom - Saleh, Nurming; Usman, Misnawaty; Sahayu, Wening (Universitas Negeri Makassar, 2023)
Abstract. This research aims to acquire data and information regarding the reading and writing competencies of college students in the German language, using Google Classroom as a teaching medium. The design employed in this study is a mixed methods approach. The research was conducted within the German Language Education Program, Department of Foreign Languages, Faculty of Language and Literature, Universitas Negeri Makassar, involving 30 fourth-semester students as the research sample. Qualitative data were obtained through participatory observation by the researcher, who observed the activities of German language learning using Google Classroom. Meanwhile, quantitative data were obtained from the average reading and writing competence test scores in the German language and t-test results. The results of participatory observation indicate that Google Classroom serves as a platform and learning space and indirectly as a tool for students to download and access course materials and complete quizzes, thereby enhancing language competency. Indirectly, this platform has become a supportive companion for students learning the German language. The quantitative data analysis revealed that students' average reading competency score is 88.8, while the writing competency score is 85.2. The t-test results also indicate that the calculated t-value for reading competency (10.975) and writing competency (8.292) is greater than the tabulated t-table (1.714). This disparity suggests that Google Classroom effectively assesses the exploration of reading and writing competencies in the German language among students. Keywords: Teaching German, Reading Competence, Writing Competence, Google Classroom